The Survivors Club: The Secrets And Science That Could Save Your Life - Ben Sherwood
Meet the members of The Survivors Club . . .The man who swam for 17 hours after falling off a cruise shipThe grandma who lifted a car to save a childThe woman who fell 33,000 feet without a parachute - and survivedIn The Survivors Club, Ben Sherwood sets out to discover what it is that helps ordinary men and women beat danger and death. What strengths do survivors share What is the science of resilience And what are the secrets of beating the oddsThis fascinating and inspiring book combines astonishing true stories, the latest scientific research and the author's own adventures inside the US military's elite survival schools to prepare you for the challenges not only of everyday life, but also for the unexpected in whatever form it takes.